IBRAYÍM YUSUPOVTÍŃ “MENIŃ ÚYIM” QOSÍǴÍN OQÍTÍWDA PSMU METODÍN QOLLANÍW - Darmenov, A. (SCIENCE and SOCIETY, 2024)
The article discusses about teaching the work of I.Yusupov in the 7th grade of secondary schools. It focuses on the importance of the method «PSMU». Students are interested in the work of the poet
Keywords: Ibrayim Yusupov; school; IREG; poetry; guest